Success factors of international sporting events in different regions of Europe - Cserháti, Gabriella; Polák-Weldon, Réka (Applied Studies in Agribusiness and Commerce, 2013)
Sport events always played an important role in human life from the ancient Olympics and marathon races to today’s modern Olympics, World and continental championships. In our days these remarkable sport events come to the fore because participants of the sporting world effectuate even more, greater and more varied ones. Furthermore, the competition for organisation between cities and countries is becoming more and more intense (Zeman 2005). The organisation of international sporting events is an extremely complicated and multiple task. The organising committee has to manage the duties and activities, to co-ordinate the participants’ work, to satisfy the needs of international sport association(s), sponsors and other stakeholders. Within the frame of the research we reveal the success factors of international sporting events in different segments of Europe, and in addition to this compare the event organization practices of analysed regions along the identified success factors. In this study we represent the results of a quantitative research, where organizers of World and European Championships – organised between 2000 and 2008 in different European countries – were asked and statistical analyses have been applied. According to our results beside the essential technical and task oriented areas the human aspects of organisation, the partnerships, coordination and communication are all-important factors. Especially in countries of East-Central Europe, where organisers have to pay more attention on selection, control of partners as well as on continuous communication with them in order to assure accurate performance in time.